2016
DOI: 10.1063/1.4953388
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of Brillouin frequency shift on water absorption ratio in polymer optical fibers

Abstract: We studied the dependence of the Brillouin frequency shift (BFS) on the water-absorption ratio in poly(methyl methacrylate)-based polymer optical fibers (POFs) to clarify the effect of the humidity on POF-based Brillouin sensors. The BFS, deduced indirectly using an ultrasonic pulse-echo technique, decreased monotonically as the water absorption ratio increased, mainly because of the decrease in the Young's modulus. For the same water absorption ratio, the BFS change was larger at a higher temperature. The max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In recent years, the discrete BOTDA [ 229 ] and chirped-pulse Φ-OTDR [ 230 ] have demonstrated their competence in detecting hydrogen with standard telecom-grade optical fiber. Moreover, specialty sensing fibers have hugely extended the potential measurands due to their unique properties, for instance, the multicore fibers and ring-core fibers for distributed curvature and bending sensing [ 231 , 232 ], the photonic crystal fibers for distributed hydrostatic pressure sensing [ 233 , 234 , 235 ], and the polymer optical fibers for distributed humidity sensing [ 236 , 237 ] and distributed radiation sensing [ 238 , 239 ]. The hybrid DOFS technology, which combines various standalone sensors to measure more abundant parameters, is a promising tool to explore further applications that will meet the requirements in many different scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the discrete BOTDA [ 229 ] and chirped-pulse Φ-OTDR [ 230 ] have demonstrated their competence in detecting hydrogen with standard telecom-grade optical fiber. Moreover, specialty sensing fibers have hugely extended the potential measurands due to their unique properties, for instance, the multicore fibers and ring-core fibers for distributed curvature and bending sensing [ 231 , 232 ], the photonic crystal fibers for distributed hydrostatic pressure sensing [ 233 , 234 , 235 ], and the polymer optical fibers for distributed humidity sensing [ 236 , 237 ] and distributed radiation sensing [ 238 , 239 ]. The hybrid DOFS technology, which combines various standalone sensors to measure more abundant parameters, is a promising tool to explore further applications that will meet the requirements in many different scenarios.…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid DOFS technology, which combines various standalone sensors to measure more abundant parameters, is a promising tool to explore further applications that will meet the requirements in many different scenarios. In addition, since the Rayleigh DOFS and the Brillouin DOFS share common measurable parameters (e.g., humidity [ 236 , 237 ]), it is possible to merge the data from both sides in a hybrid DOFS system incorporating specialty fibers, thus enabling an improved measurement performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2016, Minakawa et al further studied the relationship between the BFS of the PMMA-POF and the environmental humidity. It was observed that the BFS showed a decreasing trend with the incensement of environmental humidity and temperature, which showed the potential of detecting environmental humidity using the PMMA-POF [130]. The performance of PMMA-POFs is summarized in Table 7.…”
Section: Novel-fiber-based Brillouin Sensingmentioning
confidence: 99%